2021
DOI: 10.3390/nano11102568
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism in Au-Supported Planar Silicene

Abstract: The adsorption and substitution of transition metal atoms (Fe and Co) on Au-supported planar silicene have been studied by means of first-principles density functional theory calculations. The structural, energetic and magnetic properties have been analyzed. Both dopants favor the same atomic configurations with rather strong binding energies and noticeable charge transfer. The adsorption of Fe and Co atoms do not alter the magnetic properties of Au-supported planar silicene, unless a full layer of adsorbate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Our calculations suggest that the metal character of germanene, including the occupation of the states and the shifting of the Dirac cone with respect to the Fermi level, increases with increasing the degree of flatness of the monolayer. This point is particularly appealing in view of some recently reported planar silicene structures 24 , 25 , which suggests directing more efforts towards the synthesis of flat germanene phases for applications to terahertz device technology.…”
Section: Discussionmentioning
confidence: 99%
“…Our calculations suggest that the metal character of germanene, including the occupation of the states and the shifting of the Dirac cone with respect to the Fermi level, increases with increasing the degree of flatness of the monolayer. This point is particularly appealing in view of some recently reported planar silicene structures 24 , 25 , which suggests directing more efforts towards the synthesis of flat germanene phases for applications to terahertz device technology.…”
Section: Discussionmentioning
confidence: 99%
“…The typical spin-orbit energy in silicene has been experimentally estimated as λ so ∼ 4 meV and the buckling parameter is approximately 2l ∼ 0.46 Å [44]. Antiferromagnetism in hexagonal lattices can be introduced by the proximity effect or doping on the substrate [59][60][61]. It has been experimentally demonstrated that the antiferromagnetic exchange field can be induced in silicene via the proximity coupled to the (111) surface of the antiferromagnetic insulator BiFeO 3 .…”
Section: Experimental Feasibilitymentioning
confidence: 99%
“…The cross of the π-π* band, in turn, determines its desired physical properties. According to theoretical studies, it is possible to transform silicene into a magnetic form and use this material in spintronics applications as a spin filter or spin transistor [39][40][41]. Thanks to spin-orbit coupling and, in consequence, the relatively easy tunable bandgap, not feasible for graphene, silicene may also be considered as a valley filter in valleytronics [42][43][44].…”
Section: Introductionmentioning
confidence: 99%